Effect of Ester to Amide or N‐Methylamide Substitution on Bacterial Membrane Depolarization and Antibacterial Activity of Novel Cyclic Lipopeptides. Issue 8 (18th June 2013) - Bionda, Nina; Fleeman, Renee M.; Shaw, Lindsey N.; Cudic, Predrag
Abstract Cyclic lipopeptides derived from the fusaricidin/LI‐F family of naturally occurring antibiotics represent particularly attractive candidates for the development of new antibacterial agents. In comparison with natural products, these derivatives may offer better stability under physiologically relevant conditions and lower nonspecific toxicity, while preserving their antibacterial activity. In this study we assessed the ability of cyclic lipodepsipeptide 1 and its analogues—amide 2, N‐methylamide 3, and linear peptide 4—to interact with the cytoplasmic membranes of selected Gram‐positive bacteria. We also investigated their bacteriostatic/bactericidal modes of action and in vivo potency by using a Galleria mellonella model of MRSA infection. Cyclic lipopeptides 1 and 2 depolarize the cytoplasmic membranes of Gram‐positive bacteria in a concentration‐dependent manner. The degree of membrane depolarization was influenced by the structural and physical properties of 1 and 2, with the more flexible and hydrophobic peptide 1 being most efficient. However, membrane depolarization does not correlate with bacterial cell lethality, suggesting that membrane‐targeting activity is not the main mode of action for this class of antibacterial peptides. Conversely, substitution of the depsipeptide bond in 1 with an N‐methylamide bond in 3, or its hydrolysis to peptide 4, lead to a complete loss of antibacterial activity and indicate that the conformation of cyclic lipopeptides plays a role in their antibacterial activities. Cyclic lipopeptides 1 and 2 are also capable of improving the survival of G. mellonella larvae infected with MRSA at varying efficiencies, reflecting their in vitro activities. Gaining more insight into the structure–activity relationship and mode of action of these cyclic lipopeptides may enable the development of new antibiotics of this class with improved antibacterial activity.